EVALUASI EFEKTIVITAS PENDIDIKAN KARAKTER CINTA TANAH AIR MELALUI LAGU ANAK-ANAK - Tarmizi, Mohammad; ., Masyudi; Jamiah, Yulis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem in this research is how is the planning, implementation and result of learning evaluation through children's song in education character of homeland class V in MIS Al-Hidayah Tayan Hulu Sanggau? The method used in this research is descriptive method with qualitative approach. Techniques used in the form of direct observation techniques, direct communication techniques and taknik documentary studies. Tools used in the form of observation sheets, interview sheets and documents. The subjects of the study were educators and students of class V in MIS Al-Hidayah Tayan Hulu Sanggau. The results showed that teachers in the planning, implementation, and evaluation results of learning through children's songs in the education of the love character of the homeland class V in MIS Al-Hidayah Tayan Hulu Sanggau has been implemented well although still not maximal due to lack of ability of teachers in mastering the song children and facilities that have not been used optimally.Keywords: Evaluation, character learning, children's songs